Competitiveness in spice export trade from India: A review - P C Sanil, L Thomas, (Journal of Spices and Aromatic Crops, 2019)
Spices are one of the most traded agricultural commodities across the globe. India, as the world’s leading producer and exporter of spices is a significant stakeholder in spices export trade. The paper reviews the studies conducted on the spices export sector with special focus on India and the policy issues applicable to this sector. The review focuses on the history, trade competitiveness and issues related to regional trade agreements, trade barriers and food safety in the export trade of spices. Research gaps on issues like linkages between economic development and spice export are identified. The review concludes with suggestions for promoting growth and development of the spice export sector in India.